Development and application of educational digital contents for their access in smartphones about a statistic topic of a university course - Organista-Sandoval, Javier (2019)
This article describes the development of digital educational contents for a statistic topic that can be consulted in a smartphone. Frequently, this device is restricted in learning spaces because it is a distractor; consequently, in this article it is intended to explore the educational use of the device that can access to educational contents in a ubiquitous way. For that purpose, three topics in statistic has been developed based in the instructional design ADDIE (Analysis, Design, Development, Implementation and Evaluation). The contents were implemented in a formal course of university. The opinion of 40 students was recovered through a questionnaire with the purpose of identify the benefits and limitations in this kind of development. The results revealed that all the students have smartphones with Internet connection; this allowed them the access to that content in ubiquitous way and in advance. Among the benefits are the organization, design, functionality and utility of the consulted educational materials. The major limitations were brief explanations and limited duration in the audiovisual segments. The identified distractors were environmental noise, social media notifications and text messages. The described experience shows that the smartphone device can function as an educational tool if it is lead correctly.